Clinical Effectiveness, Safety Profile, and Pharmacokinetics of Daptomycin in Pediatric Patients: A Systematic Review. (24th August 2016) - Karageorgos, Spyridon A.; Miligkos, Michael; Dakoutrou, Maria; Tsioutis, Constantinos
Abstract: Infections by Gram-positive pathogens pose a public health risk, especially due to increasing antibiotic resistance. Daptomycin has efficacy against most clinically important Gram-positive bacteria. Although experience regarding use of daptomycin in adults is increasing, studies on pediatric populations are limited. We aimed to evaluate the efficacy, safety, and pharmacokinetics of daptomycin in pediatric settings. We searched MEDLINE and Clinicaltrials.gov (through April 2016) and included 29 original studies in the final analysis. Available evidence suggests that daptomycin in pediatric patients has a favorable safety and tolerability profile and is an efficacious alternative for treatment of Gram-positive bacteremia, endocarditis, and infections of the skin, soft tissues, joints, and bones, especially when resistant strains are involved. However, future studies need to address several issues to determine the optimal dose and various pharmacokinetic parameters in different pediatric age groups.